Management difficulties in a patient with post-traumatic stress disorder and role of trauma focused cognitive behavior therapy (Bangladesh Journal of Psychiatry, 2024)
Post-traumatic stress disorder is not uncommon but in practical ground it is really difficult to treat these patients. Multiple treatment options are in hand but psychological treatment is the first recommendation. Initially after the exposure or incident symptoms may be severe. In case of severe agitation, self-destructing behavior, intense psychological distress, extreme sleep disturbances or anger outbursts, pharmacological intervention as early as possible is needed.  Stress coping skills, relaxation therapies, psychological first aid and trauma focused cognitive behavior therapy (CBT) are important to treat the patient and get back full functional state.  Prevention of suicide and self-harm is vital. Risk assessment, presence of hostility and complete personal history guide psychiatrist to take measures. The case described below was a good example resolution by trauma focused CBT. In this case patient had severe symptoms, aggression and self-destructive behavior. By using pharmacological intervention and using all available resources of psychological therapy, patient improved.Bang J Psychiatry 2023;37(1): 20-22